2020
DOI: 10.1186/s12882-020-01886-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of soluble ST2 and soluble LR11 on mortality and cardiovascular events in peritoneal dialysis patients

Abstract: Background: Although the soluble form of suppression of tumorigenicity 2 (sST2) and soluble low-density lipoprotein receptor relative with 11 ligand-binding repeats (sLR11) have emerged as novel cardiovascular biomarkers in patients with cardiovascular disease, their prognostic value has not been fully investigated in peritoneal dialysis (PD) patients. Methods: We included 74 prevalent PD patients from a prospective cohort and measured serum sST2 and sLR11 concentrations by an enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Among the 15 studies, eight studies specifically reported dialysis patients [ 9 , 13 , 14 , 17 19 , 22 , 24 ], five studies specifically reported predialysis [ 8 , 15 , 20 , 21 , 23 ], and two studies specifically reported kidney transplant patients [ 16 , 25 ]. The main characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 15 studies, eight studies specifically reported dialysis patients [ 9 , 13 , 14 , 17 19 , 22 , 24 ], five studies specifically reported predialysis [ 8 , 15 , 20 , 21 , 23 ], and two studies specifically reported kidney transplant patients [ 16 , 25 ]. The main characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Study individuals ranged from 74 to 3,314 with a total of 11,063, and the mean or median follow-up years ranged from 1.7 to 16.2. Six studies were conducted in European countries [ 8 , 13 , 15 , 18 , 22 , 25 ], five from Asian countries [ 9 , 14 , 17 , 19 , 24 ], and the other four were carried out in America [ 16 , 20 , 21 , 23 ]. In addition, the quality of five studies was high, and another ten studies was moderate ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In hemodialysis patients, plasma IL-1RL1 (sST2) level is generally elevated and correlates with the risk of cardiovascular events and all-cause mortality observed in a one-year and three-year perspective [34]. The impact of IL-1RL1 (sST2) on cardiovascular mortality in patients treated with peritoneal dialysis was investigated by Choi et al The authors suggested that a higher IL-1RL1 (sST2) level was an independent predictor of cardiovascular mortality in this group [35]. A 2021 meta-analysis of studies conducted in CKD patients confirmed those findings [36].…”
Section: Discussionmentioning
confidence: 99%